Pendidikan Kesehatan Kanker Serviks Menggunakan Media Leaflet dalam Upaya Peningkatan Pengetahuan Ibu di Kelurahan Sukodadi Palembang - Yofa Anggriani Utama (Jurnal Abdimas Kesehatan (JAK), 2023)
Cervical cancer is a disease caused by abnormal tissue growth that occurs in the cervix, namely the lower area of the uterus that connect the uterus to the vagina. Cervical cancer is still one of the most common cancers in women and a cause of death. The implementation method is by providing health education with lecture, discussions and questions and answers, leaflet and banner, this activity was attended by 25 participants based on the results of the activity obtained by the community as many as 25 participants. The results of the implementation evaluation using a questionnaire showed that the level of knowledge before health education obtained an average score of 37.2. after the health education the average score 80.8. from the evalution results there was a change in the level of knoelegde, namely 43.6, it is hoped that mothers will be more active in partipating activities carried out to increase knowledge about health